Hacia una definición del lusitano (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The aim of this paper is to establish a corpus of linguistic elements belonging to Lusitanian language; this will be very helpfull, in turn, to comprehend in a better way the area occupied by this palaeohispanic lan- guage. Considering the texts and the local onomastics as a start point, the first elements for the corpus are proposed, and the common features are analysed.
Keywords: Lusitania; Palaeohispanic Languages; Pre-roman Languages of the Iberian Peninsula; Lusitanian Language; Celtic Languages; Onomastics; Personal Names; Divine Names; Place Names